New Biomarker Candidates of Sepsis: Diagnostic and Prognostic Value of Presepsin, Angiopoietin 1 and 2 - Yıldız, Hamit; Gül Açar, Nuray (European Journal of Therapeutics, 2024)
Objective: Sepsis is an uncontrolled inflamatory response that occurs in the body towards infection. It’s an important clinical picture that is seen in high morbidity and mortality so early diagnose and treatment areimportant. For that reason, for the septic cases to get early diagnosis and to predict the prognosis, new biomarkers are needed nowadays. Presepsin, angiopoietin 1 and angiopoietin II are biomarkers that are not usedroutinely yet, in our study, according to the new description given in Sepsis 3 meeting, in cases that are diagnosed with sepsis, we aimed at comparing diagnostic and prognostic values of these biomarkers. Methods: In our study, there were two groups. Patient group consisting of 48 cases with 33 men and 15 women and control group consisting of 42 cases with 23 men and 19 women. Control group is selected within patient relatives with similarities of age and sex. Demographic datas, accompanying diseases, APACHE II, SAPS and SOFA scores counted in the first 24 hours, leukocyte count, eritrocyte sedimentation rate, C-reactive protein, procalcitonin value, culture sampling results (blood, urine, sputum, endotracheal aspirate) that are measured in their stays, 7th and 28th day mortality counts after their ICU stays are written down. Presepsin, angiopoietin I and angiopoietin II are detected by sandwich ELISA method. Results: According to demographic features there isn’t any significant statistical difference between the patient group and the control group (p>0.005). In patient group Presepsin, angiopoietin I and angiopoietin II values were statistically high significantly compared to the control group (p<0.001). After the evaluation, serumpresepsin value noticed that has a diagnostic value in the diagnosis of sepsis (EAA: 0.74, 95%GA: 0.64–0.85, p<0.001). The suggested border value for this value is predicted as 0.47, 73%sensitivity and 62% specificity are determined. Serum angiopoietin I value noticed that has a diagnostic value in the diagnosis of sepsis (EAA: 0.80, 95%GA: 0.71–0.89, p<0.001). The suggested border value for this value is predicted as 178.24, 69% sensitivity and 69% specificity are determined. Serum angiopoietin II value noticed that has a diagnostic value in the diagnosis of sepsis (EAA: 0.89, 95% GA: 0.82–0.95, p<0.001). The suggested border value for this value is predicted as 77.56, 84% sensitivity and 83% specificity are determined. Conclusions: In our study, presepsin, angiopoietin I and angiopoietin II values are determined as statistically high according to healthy control group and are found successful with high sensitivity and specificity in diagnosing. Presepsin, angiopoietin I and angiopoietin II values in septic patients are found successful with high sensitivity and specificity at 7th and 28th days mortality prediction.